2022
DOI: 10.1111/php.13734
|View full text |Cite
|
Sign up to set email alerts
|

Senolytic Drug Quercetin Rescues Survival from Blue Light Toxicity in Drosophila Model

Abstract: With the increasing frequency of human exposure to blue light, the harmfulness of blue light has received wider attention. The damaging effect of blue light is complex and long‐lasting. In this study, Drosophila melanogaster was used as a model organism to investigate the protective effect of the senolytic drug quercetin on blue light toxicity. As one of the first senolytic drugs discovered, quercetin not only has antioxidant properties, but also has been used to treat various neurological disorders. Our study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…In another study on dexamethasone‐treated mice model, neuroprotective effects were observed after rutin administration 22 . Meanwhile, male flies sleep less and more fragmented sleep compared to females, which resembles our previous research result 23 . We believe there is a sex‐specific effect that blue light can cause more damage to male flies.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In another study on dexamethasone‐treated mice model, neuroprotective effects were observed after rutin administration 22 . Meanwhile, male flies sleep less and more fragmented sleep compared to females, which resembles our previous research result 23 . We believe there is a sex‐specific effect that blue light can cause more damage to male flies.…”
Section: Discussionsupporting
confidence: 80%
“…22 Meanwhile, male flies sleep less and more fragmented sleep compared to females, which resembles our previous research result. 23 We believe there is a sex-specific effect that blue light can cause more damage to male flies. Rutin has a very protective effect on the nervous system.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown that blue light irradiation can kill insects and that the lethal wavelengths of blue light are species-specific [6,7,16]. A few studies also demonstrated that blue light exposure negatively affected the reproduction of insects [53,58,59]. However, the mechanisms of blue light toxicity in insects remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviorally, quercetin improved lifespan and extended the time the flies voluntarily engaged in motor activity, which the authors interpreted as the health span. Quercetin also improved their heat stress survival, increased male activity levels, and boosted female egg production ( 110 ). Although blue light caused oxidative stress, senescence, and pre-mature aging in D. melanogaster , it did not specifically lead to a PD model.…”
Section: Senolytic and Senomorphic Secondary Metabolites In ...mentioning
confidence: 99%
“…Blue light irradiation is toxic to D. melanogaster by increasing oxidative stress and accelerating their aging (109). In a recent study, D. melanogaster exposed to blue light irradiation and quercetin treatment experienced a quercetin-mediated reduction of senescent cells, decreased protein content in males, and decreased lipid content in females (110). Behaviorally, quercetin improved lifespan and extended the time the flies voluntarily engaged in motor activity, which the authors interpreted as the health span.…”
Section: Quercetinmentioning
confidence: 99%